Congenital hepatic fibrosis and polycystic kidney disease not linked to C >A mutation in exon 29 of PKD1 in a Persian cat - Guerra, Juliana Mariotti; Daniel, Alexandre Gonçalves Teixeira; Cardoso, Natalia Cavalca; Grandi, Fabrizio [UNESP]; Queiroga, Felisbina; Cogliati, Bruno (SAGE Publications, 2015)
Case summary We describe the case of a 1-year-old male Persian cat diagnosed with congenital hepatic fibrosis (CHF) associated with renal polycystic disease and, for the first time, we have shown that there was no C >A mutation in exon 29 of PKD1 (polycystic kidney disease 1). The cat presented with a history of chronic weight loss, anorexia, vomiting, depression and lethargy, with profuse salivation and ascites on clinical examination. A mild elevation in liver-associated plasma enzymes suggested a hepatic disease. Owing to the cat’s deteriorating condition, it was euthanized. During necropsy, the liver was found to be enlarged, firm and reddish, and the kidney had multiple small cortical cysts. Immunohistochemistry revealed that bile duct cells and epithelial cells of renal cysts showed positive immunoreactivity to keratin 19. Collagen fibers surrounding bile ducts within portal areas demonstrated reactivity to type IV collagen antibody, confirming the congenital nature of the process. A diagnosis of ductal plate malformation consistent with CHF associated with polycystic kidney in a young Persian cat was made. Interestingly, genetic testing revealed a wild-type sequence at position 3284 in exon 29 of PKD1. Relevance and novel information The absence of the classic genetic mutation associated with the particular clinical presentation supports the hypothesis of a distinct etiopathogenesis among fibropolycystic diseases in domestic cats. Moreover, congenital hepatic fibrosis is a rare but important differential diagnosis for young Persian cats and their crosses with clinical signs of chronic end-stage liver disease.